Physiological and locomotor demands during small-sided games are related to match demands and physical fitness? A study conducted on youth soccer players - Clemente, F. M.; Silva, A. F.; Kawczynski, A.; Yildiz, M.; Chen, Y.-S.; Birlik, S.; Nobari, H.; Akyildiz, Z. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Aim The purpose of the study was: (i) to analyze the relationships of physiological and locomotor demands between small-sided games (3v3 and 5v5) and official matches (11v11); (ii) to analyze the relationships between small-sided games demands and the physical fitness of youth soccer players.